Routing performance of mobile ad hoc network in urban street-grid environment by using peer-to-peer propagation model - Ngor, Pengty (2015)
In this paper, effect of non-line of sight propagation in an urban-street environment on routing performance in mobile ad hoc network is investigated. We implement a reliable propagation model in network simulator (NS2) named peer to peer propagation model which has been shown to be suitable for our street-grid environment by taking into account non-line of sight paths. Our simulation result shows that multiple reflected signals in an urban street grid environment have significant impacts on routing performance.